Irrational use of alendronate sodium by the elderly - Camila Pereira Alvim; Roberta Carvalho Figueiredo; Camila Tavares Sousa; Ricardo Augusto dos Santos Silva; Samira Moreira Ferreira; Camilo Molino Guidoni; Paulo Roque Obreli-Neto; André Oliveira Baldoni (Sociedade Brasileira de Medicina de Família e Comunidade, 2020)
Introduction: The effectiveness and safety of alendronate sodium are dependent on patient adherence to very specific guidelines regarding use. This study aims to estimate the rational use of alendronate sodium in the elderly. Methods: This is a cross-sectional study carried out with a structured questionnaire containing form of use and occurrence of adverse events related to alendronate sodium. The patients were recruited in their own homes. Rational use was considered as being the participants who: a) took the tablet in the morning; b) were fasting; c) waited at least 30 minutes before eating; d) ingested with a full glass of water; e) ingested the whole tablet; f) and remained in the orthostatic position for at least 30 minutes after use. Additionally, the odds ratio (OR) was used to analyze the association between the irrational use of alendronate sodium and the independent variables. Results and Discussion: Of the 248 participants in the study, most of the participants administered the medication in the morning (95.2%), with fasting (89.1%), waited at least 30 minutes to eat the first meal of the day (87.9%), and were in the orthostatic position until the time of the first meal (78.6%), but less than half ingested the tablet with a full glass of water (43.6%). Rational use of the medication was observed in only 30.7% of the participants. Regarding possible adverse events, 13.3% of the participants reported some event. Among the most prevalent were dry cough (6.5%), stomach pain (5.2%) and some throat discomfort (4.8%). The irrational use of this medication is associated with age and education level. Conclusion: The prevalence of irrational use of alendronate sodium in the elderly is high, and this use is associated with patients' sociodemographic factors.